Resolubilidade global para operadores diferenciais parciais reais de ordem um - Silva, Maurício Fronza da (2006)
The present work study the global solvability of first order real linear partial diferential operators when the principal part has precisely one equilibrium point. Moreover, examples and counterexamples are presented.